Redescription of the remarkable Zhiltzovaia amabilis (Jewett, 1958) comb. nov. (Plecoptera, Perlodidae) based on types and new material from Himalaya and Pamir Mountain systems - Teslenko, Valentina A.; Palatov, Dmitry M. (Zootaxa, 2020)
Filchneria amabilis (Jewett, 1958) is recognized as a species of Zhiltzovaia Özdikmen, 2008 with the valid name Zhiltzovaia amabilis (Jewett, 1958) comb. nov., and Z. cachemirica (Aubert, 1959) is placed as a junior synonym of that species. Zhiltzovaia amabilis is redescribed from new material collected from streams of Pamir, Tajikistan, and northwestern Himalaya, northern India. New illustrations of all life stages are presented.